마이크로버블과 가시광선 레이저 조사를 통해 추출한 향부자 분획물의 용해도 개선 및 염증 완화에 관한 연구 - 정아름; Ah-reum Jung; 이지연; Ji Yeon Lee; 문소현; Sohyun Moon; 장준환; Jun-hwan Jang; 이재섭; Jae-soeb Lee; 한상배; Sang Bae Han; et al. (大韓化粧品學會誌, 2025)
본 연구는 마이크로버블 공법과 가시광선 레이저 조사 기술을 병행 적용하여 Cyperus rotundus (C.rotundus)추출물을 획득하였으며, 정제하여 얻은 향부자 정제물(major fraction from C. rotundus)을 30%(w/w) 1,3-부틸렌글라이콜에 용해하였다. 이후 레이저 조사를 차등 적용하여 향부자 마이크로버블 레이저 분획물(microbubble laser fraction from C. rotundus, MBLF-CR) 및 추가 레이저 조사를 통해 생성된 마이크로버블더블 레이저 추출 분획물(microbubble double laser fraction from C. rotundus, MBDLF-CR)을 제조하였다.제타전위 측정을 통해 분산 특성을 평가하였으며, 지표물질인 α-cyperone 함량은 HPLC 분석을 통해 확인하였다. 항염 효과 평가를 위해 Enterobacter aerogenes J2K-739 배양여과액 동결건조물(E. aerogenes J2K-739)을 RAW 264.7 세포에 처리하여 염증반응을 유도하였고, MBDLF-CR은 유도된 nitric oxide (NO) 생성 및 염증성cytokine인 IL-1β, IL-6, COX-2, 및 TNF-α의 mRNA 발현을 농도 의존적으로 감소시켰다. 본 연구를 통하여 마이크로버블 추출과 가시광선 레이저 기술의 활용 가능성을 확인하였고, 이를 적용한 향부자 추출물이 항염효능을 지닌 천연 화장품 소재로 활용 가능함을 확인하였다. In this study, Cyperus rotundus (C. rotundus) extract was obtained by applying microbubble technology and visible light laser irradiation technology in parallel, and the purified major fraction from C. rotundus (MFFC) was dissolved in 30% (w/w) 1,3-butylene glycol. Differential laser irradiation was then applied to produce the microbubble laser fraction from C. rotundus (MBLF-CR), and further irradiation yielded the microbubble double laser fraction from C. rotundus (MBDLF-CR). The dispersion characteristics of each fraction were evaluated via zeta potential analysis, and the content of the marker compound α-cyperone was quantified using high-performance liquid chromatography (HPLC). To evaluate the anti-inflammatory effects, freeze-dried culture filtrate of Enterobacter aerogenes J2K-739 (E. aerogenes J2K-739) was applied to RAW 264.7 macrophage cells to induce an inflammatory response. MBDLF-CR treatment significantly reduced nitric oxide (NO) production, as well as the mRNA expression of inflammatory cytokines, including IL-1β, IL-6, TNF-α, and COX-2, in a dose-dependent manner. Through this study, we confirmed the potential of microbubble extraction and visible light laser technology, and found that the C. rotundus extract can be used as a natural cosmetic ingredient with anti-inflammatory properties.